(untitled) (Journal of Asian Development Studies, 2024)
This study was carried out to understand how women’s emotional attachment or detachment with friends, lovers, fiancé, or spouses affect cognitive distortions among them. To gain representative results, 653 female students from six large universities in Pakistan were gaged. A checklist of emotional experiences related to attachment and detachment and a scale of cognitive distortions was utilized. After knowing the extent of emotional experiences and the level of cognitive distortion and based on path coefficient analysis (SmartPLS3), significant relationships between emotional experiences and cognitive distortions were revealed. Multiple emotional experiences showed strong positive correlations with cognitive distortion development: detachment with close friends (β = 0.31, p < 0.01), separation from fiancé/spouse (β = 0.28, p < 0.01), emotional hurt by closest ones (β = 0.35, p < 0.001), and encounters with fake love (β = 0.29, p < 0.01). The model explained 47.2% of the variance in cognitive distortions (R² = 0.472). Path analysis demonstrated that having no friends or romantic relationships significantly predicted higher levels of cognitive distortions (β = 0.26, p < 0.01). Interestingly, the breakup with the boyfriend showed an inverse relationship (β = -0.22, p < 0.05), suggesting a potential protective effect against irrational thought patterns. Theoretical implications of findings and recommendations are also discussed.